The International and Domestic Tourists Behavior in Australia: Quality vs. Quantity Issue in Regional Tourism Development Perspective - David Dean; Syifaa Novianti; Any Ariani Noor (Politeknik Negeri Bandung, 2020)
Tourism contributes to regional development and generates income for destinations. However, in many cases, the growth of tourist numbers does not necessarily result in an equivalent rise in economic contribution. The search for quality tourists over the quantity of tourists is certainly an important goal of regional development managers, but the efforts required to implement such an approach, especially the detailed documentation of tourist behavior while visiting the region, pose a challenge for most. This is perhaps why the analysis of quality vs quantity of tourists has been limited. This study focuses on the Great Ocean Road Region in Australia; an area that is experiencing increased visitor numbers but is not seeing commensurate economic growth. A fine-grained analysis of the international and domestic tourists is employed to determine behavior-based tourist quality, including the measurement of their traveling behavior, overnight visitation pattern, expenditure, and regional dispersal. Data was collected from 311 domestic tourists and 562 international tourists. Descriptive statistical methods were used in analyzing data. Results indicate that the domestic tourists were of a higher quality than the international tourists; they stayed longer, spent more, and were more widespread across the region than the international tourists. Hence, high-quality tourists can be a valuable resource and should be a priority for regional tourism development.